Prediksi Financial Distress dengan Logistik Multinominal pada Perusahaan Properti & Real Estate 2019-2023 - Debra, Jane; Suhendah, Rousilita (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2025)
This study aims to predict the condition of financial distress in property and real estate companies listed on the Indonesia Stock Exchange (IDX) during the 2019–2023 period. The analysis method used is multinomial logistic regression, with financial distress as the dependent variable and four independent variables, including profitability, liquidity, activity, and leverage. Data collection was carried out using purposive sampling on property and real estate companies that had complete financial statements throughout the study period. As a result, 55 companies were selected for the 2019–2023 period, yielding a total of 275 data samples. Data processing was conducted using IBM SPSS Statistics 25 software. The results of this study indicate that the profitability ratio does not have a significant effect on financial distress. However, liquidity and activity ratios have a negative and significant effect on the likelihood of financial distress, while the leverage ratio has a positive and significant effect on the probability of a company experiencing financial distress.